Intrinsic Restriction of TNF-Mediated Inflammatory Osteoclastogenesis and Bone Resorption - Zhao, Baohong (Frontiers in Endocrinology, 2020)
TNF is a pleiotropic cytokine that plays an important role in immunity and inflammatory bone destruction. Homeostatic osteoclastogenesis is effectively induced by RANKL. In contrast, TNF often acts on cell types other than osteoclasts, or synergically with RANKL to indirectly promote osteoclastogenesis and bone resorption. Although TNF and RANKL belong to the same super family, the direct osteoclastogenic capacity of TNF is much weaker than that of RANKL. Recent studies have uncovered key intrinsic mechanisms by which TNF acts on osteoclast precursors to restrain osteoclastogenesis. Some of these mechanisms, such as RBP-J and its mediated regulatory network, uniquely and predominantly limit osteoclastogenesis mediated by TNF but not by RANKL. As a consequence, targeting RBP-J activities suppresses inflammatory bone destruction, but does not significantly impact normal bone remodeling or inflammation. Hence, discovery of these intrinsic inhibitory mechanisms addresses why TNF has a weak osteoclastogenic potential, explains a significant difference between RANKL and TNF signaling, and provides potential new or complementary therapeutic strategies to selectively treat inflammatory bone resorption, without undesirable effects on normal bone remodeling or immune response in disease settings.